Mao's conception of the revolutionary subject - Hočevar, Marko (Asian studies, 2019)
The article explores Mao's conception of the revolutionary subject, focusing on the relationship between the peasantry and proletariat. In the years after the October Revolution, when vulgar and reductionist readings and interpretations of Marx seemed to prevail, Mao, influenced by the specific material conditions and class relations in China, conceptualised an important novelty within the Marxist tradition. Namely, he developed a very different and original understanding of the revolutionary subject, and especially a different understanding of the relationship between the proletariat and peasantry. He introduced the split between the main revolutionary subject "the proletariat" and the main revolutionary force "the peasantry". This novelty, which was unique up to that point in Marxist theory, enabled Mao to think of the Chinese revolutionary movement within a Marxist framework while considering the material conditions of life in China.
Keywords: Agricultural laborers; Communism in China; Delavski razred; Kmetijski delavci; komunizem na Kitajskem; Mao, Zedong; maoism; maoizem; Revolucije; Revolutions; Subject; Subjekt; Working class